What is Happening with the Government Expenditure of Developing Countries - A Panel Data Study - Abu Shonchoy (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
The paper focuses on the recent pattern of government expenditure for developing countries and estimates the determinants which may have influenced government expenditure. Using a panel data set for 111 developing countries from 1984 to 2004, this study finds evidence that political and institutional variables as well as governance variables significantly influence government expenditure. Among other results, the paper finds new evidence of Wagner's law which states that peoples' demand for service and willingness to pay is income-elastic hence the expansion of public economy is influenced by the greater economic influence of a nation Cameron (1978). Corruption is found to be influential in explaining the public expenditure of developing countries. On the contrary, size of the economy and linguistic fractionalization is found to have significant negative association over government expenditure. The study finds that military governments are more conservative in terms of large public expenditure other than spending on defence equipments.
Keywords: E01; E02; E61; E62; H2; H4; H5; H6; O11; O5; 330; Government expenditure; Panel data; Corruption; Fractionalization; Governance.